2004
DOI: 10.1200/jco.2004.02.121
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Therapy and Autologous Hematopoietic Stem-Cell Transplantation for Recurrent or Refractory Pediatric Hodgkin's Disease: Results and Prognostic Indices

Abstract: More than half of children with relapsed or refractory HD can be successfully treated with the combination of high-dose therapy and AHSCT, confirming the efficacy of this approach. Further investigation is now required to determine the optimal timing of AHSCT, as well as to develop alternative regimens for those patients with factors prognostic for poor outcome after AHSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
99
3
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 64 publications
4
99
3
1
Order By: Relevance
“…Our group did mandate some evidence of chemosensitivity before receiving HDM and auto-SCT, in contrast to many other published reports, which may have biased our results towards better outcomes. 4,6,7,12,14,17 However, a review of our institutional registry from 1991 to 2009 revealed that no patient was ineligible for HDC because of the suboptimal response to salvage chemotherapy. The single patient in our series with stable disease pretransplant did have radiographic evidence of reduction in disease, but did not constitute a PR.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our group did mandate some evidence of chemosensitivity before receiving HDM and auto-SCT, in contrast to many other published reports, which may have biased our results towards better outcomes. 4,6,7,12,14,17 However, a review of our institutional registry from 1991 to 2009 revealed that no patient was ineligible for HDC because of the suboptimal response to salvage chemotherapy. The single patient in our series with stable disease pretransplant did have radiographic evidence of reduction in disease, but did not constitute a PR.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]6 More commonly used conditioning regimens in adults and children have achieved event-free survival rates between 40 and 60%. 2,[4][5][6]10,12,15 Although the NRM for those with HL treated with auto-SCT has decreased with time, the use of HDC with or without RT is not without toxicity. The NRM with CBV þ /ÀP has been reported between 23 and 26%, and when second malignancies are excluded, has been reported between 5 and 14%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations